Ответы и объяснения

  • fuflunce
  • почетный грамотей
2013-01-09T12:11:05+00:00

cos(П/2 + x) = -sinx = 12/13

sinx = -12/13

cosx = корень из (1 - sin^2x) = корень из (1 - 144/169) = корень из 25/169 = 5/13

т.к. x принадлежит промежутку (  ;  ), то cosx = -5/13

tg2x = 2tgx/(1 - tg^2x) 

tgx = sinx/cosx = (-12/13)/(-5/13) = 12/5

tg2x = 2*(12/5)/[1 - (12/5)^2] = (24/5)/(-119/25) = -120/119

Лучший Ответ!
  • IZUBR
  • светило науки
2013-01-09T13:43:34+00:00

Так, это тоже решил, все относительно просто: